2021
DOI: 10.1002/slct.202101163
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐Responsive Fe3O4@MSN@PPy‐PVP Nanoparticles as the Nano‐Enzyme for Potential Tumor Therapy

Abstract: Among various kinds of photothermal conversion materials, polypyrrole (PPy) has attracted ever-increasing attention because of its good biocompatibility and excellent near-infrared light response property. In this research, the core-shell nanoparticles with magnetic Fe 3 O 4 as the core and mesoporous silica (MSN) as the shell were prepared, the resulted Fe 3 O 4 @MSN nanoparticles were then surface coated with a layer of PPy and further modified with polyvinylpyrrolidone (PVP) to gain colloidal stability. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…S6, ESI †). It is observed that after the addition of GG@PANI(Fe), the o-phenanthroline (phen) molecules formed deep orange [Fe(phen) 3 ] 2+ complexes with a distinct characteristic peak at 510 nm, 49 indicating the existence of Fe 2+ ions in the GG@PANI(Fe) composite. Besides, according to the calculation by TG analysis (Fig.…”
Section: Paper Journal Of Materials Chemistry Bmentioning
confidence: 99%
“…S6, ESI †). It is observed that after the addition of GG@PANI(Fe), the o-phenanthroline (phen) molecules formed deep orange [Fe(phen) 3 ] 2+ complexes with a distinct characteristic peak at 510 nm, 49 indicating the existence of Fe 2+ ions in the GG@PANI(Fe) composite. Besides, according to the calculation by TG analysis (Fig.…”
Section: Paper Journal Of Materials Chemistry Bmentioning
confidence: 99%
“…Polypyrrole (PPy) is a promising photothermal agent for cancer therapy that has attracted increasing attention in the design of smart MSNs thanks to its good biocompatibility and excellent near-infrared light response property. Wang and collaborators [ 128 ] reported the polymerization of PPy on the external surface of magnetic Dox-loaded MSNs (Fe 3 O 4 @MSN@PPy-PVP@DOX). The obtained devices, in in vitro and in vivo experiments, showed a good inhibition of cancer cell growth due to the synergism of photothermal-, chemo- and chemodynamic therapy.…”
Section: The Multifunctional Project Using Msnsmentioning
confidence: 99%
“…The troubleshooting of this problem is done by grafting the nonionic surfactant poly(vinylpyrrolidone) (PVP) onto PPy NPs. 25 PVP is a polymer that offers a unique approach for enhancing the stability of NPs and is authorized by the Food and Drug Administration of the United States (U.S. FDA). 26 In addition, TAT peptide, a kind of nuclear localization signal (NLS), is an efficient molecule for translocating PPy into cell nuclei by interacting with receptors, i.e., importin α and β (karyopherin), further targeting nuclear pore complexes (NPCs), and finally entering the nuclei.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, pure PPy NPs have weak aqueous solubility, which limits their use in tumor PTT. The troubleshooting of this problem is done by grafting the nonionic surfactant poly­(vinylpyrrolidone) (PVP) onto PPy NPs . PVP is a polymer that offers a unique approach for enhancing the stability of NPs and is authorized by the Food and Drug Administration of the United States (U.S. FDA) .…”
Section: Introductionmentioning
confidence: 99%